2020
DOI: 10.1007/s00127-020-01928-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anxiety of otolaryngology healthcare workers in Hubei province fighting coronavirus disease 2019 (COVID-19)

Abstract: Purpose To ensure the mental health of the otolaryngology healthcare workers in the fight against coronavirus disease 2019 (COVID-19), it is important to know their mental status and to identify possible risk factors. In this study, we investigated the risk factors for the anxiety in the otolaryngology healthcare workers in Hubei province under the COVID-19 epidemic. Methods The otolaryngology healthcare workers in Hubei Province were surveyed using an online questionnaire in which anxiety was measured against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
0
26
0
3
Order By: Relevance
“…Direct contact with COVID-19 patients was associated with poor mental health outcomes, 8,13,31,35,36,43,45,46,47,48 as well as personal fear of infection and perceived threat of contagion. 13,21,22,27,32,37,49,50,51 These adverse outcomes were also seen in HCWs with friends or family with COVID-19 infection 22,32,33,34,49 and in HCWs with colleagues who were hospitalized or died of COVID-19. 39 Further, working in COVID-19 designated hospitals compared to non-designated hospitals 25,49,52 and working in COVID-19 specific isolation wards 13,22,40,45 were associated with poorer mental health outcomes.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Direct contact with COVID-19 patients was associated with poor mental health outcomes, 8,13,31,35,36,43,45,46,47,48 as well as personal fear of infection and perceived threat of contagion. 13,21,22,27,32,37,49,50,51 These adverse outcomes were also seen in HCWs with friends or family with COVID-19 infection 22,32,33,34,49 and in HCWs with colleagues who were hospitalized or died of COVID-19. 39 Further, working in COVID-19 designated hospitals compared to non-designated hospitals 25,49,52 and working in COVID-19 specific isolation wards 13,22,40,45 were associated with poorer mental health outcomes.…”
Section: Resultsmentioning
confidence: 90%
“…13,21,22,27,32,37,49,50,51 These adverse outcomes were also seen in HCWs with friends or family with COVID-19 infection 22,32,33,34,49 and in HCWs with colleagues who were hospitalized or died of COVID-19. 39 Further, working in COVID-19 designated hospitals compared to non-designated hospitals 25,49,52 and working in COVID-19 specific isolation wards 13,22,40,45 were associated with poorer mental health outcomes. However, smaller single-institution studies in Romania 53 and in Guangzhou, China, 54 where there were fewer COVID-19 cases, did not find differences in mental health outcomes between HCWs working in dedicated versus non-dedicated wards.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…China is the first country to be severely affected by COVID-19, and the mental health of Chinese frontline medical staff has been greatly affected. A considerable proportion of Chinese healthcare workers have reported symptoms of depression (25.2%-58%), anxiety (29.18%-54.2%), or insomnia (34.0%-36.1%) during the COVID-19 epidemic [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…During the epidemic, the public was faced with mandatory quarantines, possible economic losses, and unexpected unemployment, all of which can increase anxiety, depression, and insomnia [10,16]. Previous studies reported that 14.6%-17.2% and 6.3%-28.8% of the Chinese general public displayed symptoms of depression or anxiety, respectively, during the epidemic [18][19][20]; these prevalences are lower than the prevalence of depression and anxiety among Chinese medical staff [11,13,14]. Compared to the general public, medical workers have been challenged by higher levels of exposure to the epidemic situation and by overwork [5,21]; thus, the mental health of medical workers may be more affected by COVID-19 than that of the general public.…”
Section: Introductionmentioning
confidence: 99%